A Study of AGV Collaboration with IoT Concept to Avoid a Collision at Warehouse Intersection - Rizky Muftygendhis; Wei Jung Shiang; Chia Hung Hsu (Logistic and Operation Management Research (LOMR), 2022)
Technology nowadays is always changing very fast. Automated tools are used to face the advanced technology in the warehouse industry, such as automated guided vehicles (AGV). It becomes a common daily vehicle when working in the warehouse, especially on the shop floor. It means collaboration between AGVs is needed and has become important. This paper suggests how to avoid collisions between AGVs and how to avoid obstacles is a practical problem if two or more AGVs interact with each other. This is a common need that should be addressed. As a result, a more effective system design should be created and implemented. This paper used a three-tier internet of things (IoT) structure to avoid collisions and reduce path deviation to design an AGV collaboration system. The IoT was used to authorize AGVs to communicate with each other by transmitting position messages. In this situation, AGV would be aware of other AGV positions and would decide what to do next. According to the findings, two AGVs can avoid colliding by knowing each other's positions in any path scenario by recognizing obstacles through Light Detection and Ranging (LIDAR) detection. This paper designed an AGV collaboration system using the Robot Operating System (ROS) and conducted an experiment to test its practicality. The experiment simulated a warehouse intersection in the real world. This study used the statistical ANOVA method to identify motion planning parameters concerning final AGV position error values.